Penilaian Kualitas Tanah Menggunakan Indeks Kualitas Tanah (Soil Quality Index/SQI) di Sekitar TPA Sukawinatan dan TPA Indralaya, Sumatera Selatan - Leviana; Sabaruddin; Haya F Nabilah; Tedy Satriadi (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian Universitas Andalas, 2026)
Inadequate solid waste management contributes to soil degradation through increasing acidity, declining organic matter, heavy-metal accumulation, and disruption of soil microbial activity. These impacts are commonly observed around landfill sites, especially in regions with high waste generation. This study aims to assess and compare the Soil Quality Index (SQI) of two landfill areas representing contrasting regional characteristics: Sukawinatan Landfill in Palembang City and Indralaya Landfill in Ogan Ilir Regency. Soil samples were collected at varying distances from the waste mound, and several soil quality parameters—organic matter, total nitrogen, pH, available phosphorus, and moisture content—were analysed. The SQI was calculated using a weighted integration method to provide an overall evaluation of soil health at each site. The results show that the Sukawinatan Landfill exhibits lower SQI values than the Indralaya Landfill, indicating more severe soil degradation due to greater waste volume and higher operational intensity. Increasing distance from the waste pile improved soil quality, although recovery patterns differed between locations. These findings highlight the need for improved waste-management practices and routine soil monitoring to prevent further environmental degradation. The study provides important insights for policy formulation related to landfill management, particularly in urban and peri-urban areas. Key words : Indralaya, Palembang, soil quality, solid waste, Soil Quality Index